Economic and food security impacts of climate disasters and mitigation policies: Insights from Nigeria - Escalante, Luis Enrique; Mamboundou, Pierre; Meyimdjui, Carine; Omoju, Oluwasola E. (Springer, 2025)
Climate disasters, exacerbated by climate change, are becoming more frequent and severe, leading to significant socioeconomic and food system implications. Using econometrics and a dynamic general equilibrium model, this study examines the economic impact of climate disasters in Nigeria and evaluates the effect of mitigation strategies. The results show that the direct effects of climate disaster shocks on crop production spill over to other sectors of the economy, resulting in an overall 2.11% fall in real GDP. The analysis also highlights the substantial influence of climate disasters on Nigeria’s food systems and the consequent increase in food insecurity, particularly in the northern region, where the likelihood of food shortages increases by 6.50%. The analysis of mitigation measures suggests that a mix of policies is more efficient than stand-alone policies. Specifically, we found that a combined strategy of cash transfers for rural households and tax reductions for urban households is the best option, as it improves consumption and employment. However, it also leads to increased food imports and vulnerability. Complementing this strategy with targeted investments and subsidies is key to strengthening crop resilience and mitigating disaster impacts.